PASTORAL KONSELING BAGI KESEHATAN MENTAL “STUDI KASUS PASTORAL KONSELING PREVENTIF PADA FENOMENA BUNUH DIRI” - Ryanto Fadly Sumendap; Theresia Tumuju (Institut Agama Kristen Negeri Manado, 2023)
Suicide is a serious problem that affects many individuals worldwide. Poor mental health often serves as a major risk factor in suicide cases. In suicide prevention efforts, mental health plays a crucial role that needs to be addressed. This study aims to examine the role of mental health as a preventive factor in suicide cases from the perspective of pastoral counseling. In this research, the pastoral counseling approach is used as a framework to analyze how preventive efforts in the field of mental health can be carried out through pastoral guidance and support. This approach acknowledges the complexity of individuals as beings with physical, emotional, social, and spiritual dimensions. In pastoral counseling, it is important to understand and appreciate the diversity of individuals and provide a safe, supportive, and non-judgmental environment. Through the pastoral counseling approach, suicide prevention efforts can involve education and awareness about mental health, the development of adaptive coping skills, the provision of emotional support, and the fostering of trusting relationships between counselors and clients. Pastoral counselors can also assist individuals in identifying and addressing risk factors associated with poor mental health, as well as providing effective strategies for managing stress and improving quality of life. The results of this study indicate that good mental health is a preventive key in suicide cases. Within the framework of pastoral counseling, suicide prevention efforts can be conducted by considering mental health aspects holistically and integrating theological and counseling understandings. This research contributes significantly to strengthening the role of pastoral counseling in suicide prevention and promoting awareness of the importance of maintaining comprehensive mental health.